Analisa Visualisasi Data Penjualan dan Tingkat Kepuasan Penjualan Menggunakan Platform Lookerstudio - Arfandi, Zirhan; Yanto, Budi; Sabri, Khairul; Aini, Yulfita; Lubis, Adyanata (Fakultas Ilmu Komputer, Universitas Pasir Pengaraian, 2024)
Data management in projects is an important activity in a company because over time the company develops more and more versatile data it has. Growing and highly complex business and supply of goods on a large scale makes data processing difficult. In the current situation, data processing starting from exporting, filtering data, analyzing and visualizing data is still done using Excel files which takes quite a long time, so that management decision making is still not optimal. . The purpose of this research is to provide users with important information and data in real time to speed up the decision-making process. Therefore, the data must be analyzed using the exploratory data analysis (EDA) method. EDA is carried out starting from understanding business objects, with revenue/sales as one of the metrics used to see the company's performance profile and the correlation of other variables. target knife The results of this study indicate that monthly sales comparisons, sales comparisons for each product and composition have the lowest sales generation and customer satisfaction, so that they can be used as material for management evaluation and EDA results can be seen in data visualization applications